2020
DOI: 10.1111/joms.12617
|View full text |Cite
|
Sign up to set email alerts
|

Sensemaking, Organizing, and Surpassing: A Handoff*

Abstract: In this essay, I reflect on the intellectual influences that led to the genesis of the Social Psychology of Organizing and assess the way forward. I stress that the Social Psychology aspired to provide an outline of an organizational epistemology. I particularly focus on the interplay between experience and understanding, highlighting the following features: self-validating prophecy, partiality toward similarity, ambivalence between belief and doubt, and understanding as ongoing accomplishment. I conclude with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 29 publications
0
43
0
2
Order By: Relevance
“…As has been emphasized earlier in this article, managers have an important role in facilitating communication and sensemaking. Weick (2020) reminds us that organizing is ultimately an interpersonal communication process that brackets and stabilizes some parts of an everchanging and complex reality. An alternative route could have been to openly acknowledge the vague role and focus on joint conversations to reduce this ambiguity.…”
Section: Internal Crisis Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been emphasized earlier in this article, managers have an important role in facilitating communication and sensemaking. Weick (2020) reminds us that organizing is ultimately an interpersonal communication process that brackets and stabilizes some parts of an everchanging and complex reality. An alternative route could have been to openly acknowledge the vague role and focus on joint conversations to reduce this ambiguity.…”
Section: Internal Crisis Communicationmentioning
confidence: 99%
“…During Weick's whole career, he has claimed that organizations and humans are not as rational as usually thought, and this understanding is the root of many organizational problems. Weick (1969Weick ( , 2020 claims that instead we must understand the process of sensemaking, and that we socially construct a reality that we act on. Weick (1995) argues that there are two types of sensemaking occasions common to organizationsuncertainty and ambiguity.…”
Section: Leadership Sensemaking and Communication In Crisesmentioning
confidence: 99%
“…Sensemaking theory argues that constructing such information into sensible accounts is driven by plausibility, but what makes something 'plausible' is worth re-examining. Early work on sensemaking suggested that dissonance reduction contributed to perceived plausibility (Weick, 1995) but this notion remains understudied (Weick, 2020). Most sensemaking research has adopted an evolutionary perspective, which assumes that sensemaking becomes more plausible as it 'becomes more comprehensive, incorporates more of the observed data, and is more resilient in the face of criticism' (Weick et al, 2005, p. 415).…”
Section: Meaning-makingmentioning
confidence: 99%
“…However, the current emergency has dragged on with an impact that fuels collective and individual discomfort and illness as well as difficulties in creating ever new meanings and adaptive responses (Weick, 2020 ). Therefore, the phases describing the effects of disasters are only partially adequate to explain this historical moment because the disillusionment phase is not yet fully visible due to the recursive nature of the present pandemic.…”
Section: Introductionmentioning
confidence: 99%